2012
DOI: 10.1093/cercor/bhs326
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Neural Correlates of Intention and Action Preparation in Voluntary Task Switching

Abstract: This electroencephalographic (EEG) study investigated the impact of between-task competition on intentional control in voluntary task switching. Anticipatory preparation for an upcoming task switch is a hallmark of top-down intentional control. Meanwhile, asymmetries in performance and voluntary choice when switching between tasks differing in relative strength reveal the effects of between-task competition, reflected in a surprising bias against switching to an easier task. Here, we assessed the impact of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
64
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 58 publications
7
64
3
4
Order By: Relevance
“…Thus, Vandamme et al (2010) claimed this increased CNV-like activity to be an index of intentional preparation for voluntary switching. In a recent study, Poljac and Yeung (2014) further demonstrated that between-task competition could modulate voluntary intentional control, as revealed by two distinct components in their difficult asymmetric task design (i.e., the easy location task vs. the hard shape task). When additional intentional control was involved in switching to the paradoxically easy task, a right-lateralized frontal CNV was identified to mirror the greater asymmetric switch costs.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, Vandamme et al (2010) claimed this increased CNV-like activity to be an index of intentional preparation for voluntary switching. In a recent study, Poljac and Yeung (2014) further demonstrated that between-task competition could modulate voluntary intentional control, as revealed by two distinct components in their difficult asymmetric task design (i.e., the easy location task vs. the hard shape task). When additional intentional control was involved in switching to the paradoxically easy task, a right-lateralized frontal CNV was identified to mirror the greater asymmetric switch costs.…”
Section: Introductionmentioning
confidence: 97%
“…Следует отметить, что оперативная память служит для вре-менного хранения и использования информации и играет ключевую роль в процессах долговременной памяти, правильного использования и понимания речи, а также в реализации исполнительных функ-ций через двигательную активность [9][10][11].…”
unclassified
“…В настоящее время господствует гипотеза о том, что временной процессинг (т.е. об-работка) промежутков, измеряемых субсекундным диапазоном, модулируется допаминергической ак-тивностью базальных ганглиев, что очень важно для понимания происхождения нарушений двига-тельной активности и функционального статуса [5,8,11,[13][14][15][16][17][18][19][20][21][22].…”
unclassified
See 2 more Smart Citations